Routing policies in multi-parallel warehouses: An analysis of computing times (2017)
In this paper, we study the computation time of routing policies for the picker routing problem in order to determine the feasibility of the simultaneous use of these policies in picking problems. For this, programming details of routing policies are shown, and simulations considering different warehouse sizes and pick list sizes are performed. Taking into account different population sizes and numbers of iterations, the computation time of routing policies in population-based metaheuristics for the order batching problem is estimated. © 2017.